Legal Implication of Quran Chapter 4 Verse 3 on Muslims' Marital Affairs - Ahmed Abiodun Muhammed-Mikaaeel (Jurnal Hukum Novelty, 2021)
Introduction to The Problem: Bad practice of polygyny among certain members of Muslim Ummah is nothing to write home about. The practice does not conform to Islamic teachings as contained in the unambiguous provision of the ordinance in Quran Chapter 4 verse 3. The very essence of Islamic polygyny, which is geared towards protecting the interest of widows and orphan girls, is defeated among the bad practitioners of polygyny. This has resulted in ardent opposition to the practice of Islamic polygyny. The foregoing informs the reason this paper examines the legal implication of Chapter 4 verse 3 on Muslims’ marital affairs.Purpose/Objective Study: The objective of this paper is to examine the genesis and subject matter of Chapter 4 verse 3, the legal implication of Chapter 4 verse 3, and the juristic opinion on Islamic polygyny, the Muslims bad practice vis-à-vis the reality on Islamic polygyny.Design/Methodology/Approach: The methodology employed in this paper is simply the doctrinal method of legal research. To the end, the paper relies the provisions of the Quran, Hadith, Juristic Views, and scholarly articles written on the subject matter of this paper.Findings: The paper reveals that the primary objectives of the legal implication of Chapter 4 verse 3 include the protection of widows, orphan girls and divorcees; abolition of unjust/bad practices in marital affairs; payment of adequate dowry to women in the event of marriage irrespective of whose ox is gored; and satisfaction of man’s desire for women and outright abolition of Zina. The paper discovers that the practice of polygyny has continued to be relevant in view of the incessant pressing needs for it. The paper also finds that the greatest challenges to Islamic polygyny are inherent in the Muslim Ummah, both on the parts of men and women. The paper recommends character adjustment for both sexes to pave the way for the true practice of Islamic polygyny.Paper Type: Research Article